Analisis Perbandingan Kinerja Keuangan antara PT. Bank Central Asia Tbk. dengan PT. Wahana Ottomitra Multiartha Finance Tbk. Periode 2011-2021 - Intani Puteri Syarifah; Diyah Khoirunnisa; Luthfi Isnaini Afifah; Darmawan Darmawan; Achmad Jufri (LPPM - STIE SAKTI ALAM KERINCI, 2022)
The puprose of this study is to determine the financial performance of PT. Bank Central Asia Tbk. and PT. Wahana Ottomitra Multiartha Finance Tbk. Research is useful for the company as input on financial statements in terms of assessing the company’s performance to make decisions in the future. This research is also useful for researchers to know the importance of financial statements to evaluate performance. This research uses quantitative methods. The data source used is is accessed through the www.idx.co.id website as the official website of Indonesia Stock Exchange. The data type used is secondary data from PT. Bank Central Asia Tbk. and PT. Wahana Ottomitra Multiartha Finance Tbk. in the form of financial report data and annual reports that have been published from 2011 to 2021. The research period was conducted during November 2022. The analytical techniques used are liquidity ratios, solvency, and profitability. Based on the analysis of financial performance measured in the form of LDR, LAR, PR, ROA, and ROE, it can be seen that PT. Bank Central Asia Tbk. is in better condition than PT. Wahana Ottomitra Multiartha Finance Tbk. The management of the two companies should maintain their financial performance even though it is still said to be good.